Association Between Type of Reconstruction After Mohs Micrographic Surgery and Surgeon‐, Patient‐, and Tumor‐Specific Features: A Cross‐Sectional Study. Issue 1 (30th November 2012) - Alam, Murad; Helenowksi, Irene B.; Cohen, Joel L.; Levy, Ross; Liégeois, Nanette; Mafong, Erick A.; Mooney, Maureen A.; Nehal, Kishwer S.; Nguyen, Tri H.; Ratner, Desiree; Rohrer, Tom; Schmults, Chrysalyne D.; et al.
Abstract : Background: There are few data to indicate whether the type of final wound defect is associated with the type of post‐Mohs repair. Objective: To determine the methods of reconstruction that Mohs surgeons typically select and, secondarily, to assess the association between the method and the number of stages, tumor type, anatomic location, and patient and surgeon characteristics. Methods: Statistical analysis of procedure logs of 20 representative young to mid‐career Mohs surgeons. Results: The number of stages associated with various repairs were different (analysis of variance, p  < .001.). Linear repairs, associated with the fewest stages (1.5), were used most commonly (43–55% of defects). Primary repairs were used for 20.2% to 35.3% of defects of the nose, eyelids, ears, and lips. Local flaps were performed typically after two stages of Mohs surgery (range 1.98–2.06). Referral for repair and skin grafts were associated with cases with more stages (2.16 and 2.17 stages, respectively). Experienced surgeons were nominally more likely perform flaps than grafts. Regression analyses did not indicate any association between patient sex and closure type ( p  = .99) or practice location and closure type ( p  = .99). Conclusions: Most post‐Mohs closures are linear repairs, with more bilayered linear repairs more likely at certain anatomic sites and after a larger number of stages.